Carbon Footprint Report 2020 : Greenhouse gas emissions resulting from EIB Group internal operations - European Investment Bank (European Investment Bank, 2021)
This report provides a comprehensive breakdown of EIB Group greenhouse gas emissions arising from internal operations at head office locations in 2020. It also analyses comparatively against performance in previous years dating back to the 2007 baseline. As a result of the teleworking arrangements during the COVID-19 pandemic, the EIB Group$1 (Bs net emissions in 2020 were more than 70% below 2019 levels.s
Knowledge Unlatched
English
Keywords: Climate change; Science; Global Warming & Climate Change